Effect of acid leaching of bamboo and hardwood chips on kraft pulping and pulp bleaching (Bangladesh Journal of Scientific and Industrial Research, 2016)
Acid leaching of chips prior to pulping is a proven method to reduce non-process elements in kraft pulping process. In this paper, acid leaching of bamboo and hardwood chips was carried out at pH 2 for 1h at 80 °C prior to kraft pulping. Calcium removal in acid leaching from wood chips was 52.6% while for bamboo was only 17.4%. Acid leaching also reduced potassium (K) from 1258 mg/kg to 495.7 mg/kg for bamboo and 928 mg/kg to 562.5 mg/kg for wood chips. The effects of acid leaching on pulping, pulp bleaching, and papermaking characteristics were also determined. Acid leaching of both kinds of chips prior to kraft cooking resulted in a significant increase in the rate of delignification. Acid leached chips showed higher screen pulp yield and lower rejects at any kappa number. There was no significant difference of papermaking properties between pulps obtained from acid leached and non-leached chips. Using same ClO2 charge, acid leaching improved pulp brightness by 1% and 1.1% for hardwood and bamboo, respectively. Acid leaching improved pulp viscosity from 10.1 mP.s to 12.1 mP.s for hardwood.Bangladesh J. Sci. Ind. Res. 51(4), 247-252, 2016